1982
DOI: 10.1172/jci110435
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Direct Stimulatory Effect of Prostacyclin on Renin Release in Man

Abstract: A B ST R A C T The objectives of this investigation were: (a) to characterize the time and dose dependence of the effects of prostacyclin (PGI2) on renin release in healthy men; (b) to define whether PGI2-induced renin release is secondary to hemodynamic changes; (c) to determine the plasma and urine concentrations of 6-keto-PGFIa (the stable breakdown product of PGI2) associated with renin release induced by exogenous or pharmacologically enhanced endogenous PGI2. Intravenous PGI2 or 6-keto-PGFIa infusions at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0
1

Year Published

1984
1984
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(67 citation statements)
references
References 21 publications
4
62
0
1
Order By: Relevance
“…Changes in renal synthesis of PGI2 and/or PGE could explain the prostaglandin related events that occur in the kidney after frusemide in view of their known ability to increase renal blood flow and renin secretion (McGiff, 1980). Although in this study there was no correlation between the excretion rates of urinary PGE and the changes in these parameters after frusemide the time course of change in excretion of both 6-keto-PGFIa and PGE previously demonstrated by others (Scherer & Weber, 1979;Patrono et al, 1982) and confirmed here with respect to PGE, provides further support for such a relationship. Urinary PGE excretion provides a measure of renal PGE synthesis (Frolich et al, 1975).…”
Section: Prostaglandins and Frusemide 517mentioning
confidence: 47%
“…Changes in renal synthesis of PGI2 and/or PGE could explain the prostaglandin related events that occur in the kidney after frusemide in view of their known ability to increase renal blood flow and renin secretion (McGiff, 1980). Although in this study there was no correlation between the excretion rates of urinary PGE and the changes in these parameters after frusemide the time course of change in excretion of both 6-keto-PGFIa and PGE previously demonstrated by others (Scherer & Weber, 1979;Patrono et al, 1982) and confirmed here with respect to PGE, provides further support for such a relationship. Urinary PGE excretion provides a measure of renal PGE synthesis (Frolich et al, 1975).…”
Section: Prostaglandins and Frusemide 517mentioning
confidence: 47%
“…(1) (Patrono, 1980) and urinary 6-keto-PGFI, as an index of renal epoprostinol (PGI2) production (Patrono et al, 1982). The finding that indomethacin reduced both, whereas sulindac inhibited only serum TXB2, confirms that sulindac exerts a selective inhibition of prostaglandin synthesis (Ciabattoni et al, 1980).…”
Section: Discussionmentioning
confidence: 94%
“…However, these conclusions must be drawn with caution for the following reasons: (a) the small number of patients studied; (b) sulindac reduced PRA as did indomethacin, an unexpected finding, considering the known role of PGI2 in the stimulation of renin secretion (Ciabattoni et al, 1980;Patrono et al, 1982); (c) although sulindac significantly reduced (circa 75%) serum TXB2, this effect was significantly (P < 0.01) less than that exerted by indomethacin which reduced it by about 95%.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of renal excretion of 6-keto-PGFI, illustrates this situation. This prostaglandin was selected because it is the stable metabolite of PGI2 (Schlondorff & Ardaillou, 1986), mainly synthesised by the kidney (Patrono et al, 1982), and because prostacyclins play a determinant role in renal blood flow regulation (Dunn, 1987). Predictably (Carmichael & Shankel, 1985), pretreatment by KP significantly reduced renal excretion of 6-keto-PGF,C.…”
Section: Discussionmentioning
confidence: 99%